Nephrotoxicity induced by dichlorovos and protection by Zingiber Officinale in male rats - BHAWANA SHARMA; PRIYANKA SHARMA; S.C. JOSHI (International Journal of Pharma and Bio Sciences, 2018)
Dichlorovos (DDVP) is an extensively used organophosphate insecticide for crop protection against pests and also in various public health operations. Many studies reported that enzymatic and non-enzymatic antioxidant may play protective role against dichlorovos induced toxicity in mammals. The aim of the present study was to investigate the protective effects of Zingiber officinale induced nepherotoxicity in male rats. Rats were divided into four groups containing six rats in each group. Group I served as control. Group II, III and IV were treated with aqueous extract of Zingiber officinale (AGE) (200 mg /kg bwt); dichlorovos 20 mg/kg bwt (1/20 LD50); dichlorovos (20 mg/kg bwt) plus Zingiber officinale (200 mg/kg bwt) respectively. Rats were orally administered with their respective doses daily for 45 days. Dichlorovos administration to rats resulted in significant reduction in body weight and kidney weight compared to control. Dichlorovos caused significant elevation of blood urea and serum creatinine levels. Oral administration of dichlorovos induced various histological changes in the kidney. These changes include severe deterioration of glomerulus along with degenerated visceral layer. Vacuolization of renal tubules is also visible with increase capsular space. Histopathological studies of kidney revealed that supplementation of AGE resulted in mild degeneration and necrosis of the renal tubules. Animals when treated with aqueous extract of Zingiber officinale and dichlorovos showed improvement in the renal changes induced by dichlorovos together with significant decrease in blood urea and serum creatinine levels. The results of the present work indicated that Zingiber officinale (ginger) possess protective effect against liver damage induced by dichlorovos which was possibly due to its antioxidant activities.